If, At First, The Idea is Not Absurd, Then There is No Hope For It: Towards 15 MtC in the UK Transport Sector - Robin Hickman; David Banister (European Regional Science Association (ERSA), 2005)
This paper examines the possibilities of reducing transport carbon dioxide emissions in the UK by 60 per cent by 2030 using a modified scenario building and backcasting approach. It examines a range of policy measures (behavioural and technological), assessing how they can be effectively combined to achieve the required level of emissions reduction. The intention is to evaluate whether such an ambitious target is feasible, identify the main problems (including the transition costs), and the main decision points over the 30-year time horizon. This paper outlines the first stages of the research, providing: An introduction to futures studies, including a review of forecasting, scenario building and backcasting approaches; An assessment of the UK transport sector's contribution to climate change and global warming, and; Setting targets for 2030, forecasting the business as usual situation for all forms of transport in the UK, and assessing the scale of change in terms of achieving the emissions reductions. The benefits of scenario building and backcasting are that innovative packages of policy measures can be developed to address emissions reduction targets. It allows trend-breaking analysis, by highlighting the policy and planning choices to be made by identifying those key stakeholders that should be included in the process, and by making an assessment of the main decision points that have to be made (the step changes). It also provides a longer-term background against which more detailed analysis can take place.
Keywords: 330